Toward reciprocity: host supervisor perspectives on international medical electives. Issue 4 (April 2014) - Bozinoff, Nikki; Dorman, Katie P; Kerr, Denali; Roebbelen, Erica; Rogers, Erin; Hunter, Andrea; O'Shea, Tim; Kraeker, Christian
<x xml:space="preserve">Abstract</x> Discuss ideas arising from the article at 'discuss'